Convenience in Paying Dam (Penalty) in Making Hajj: A Perspective Aligned with the SDGs - Mariati Aprilia Harahap; Dodik Siswantoro; Muhamad Abduh (Universitas Muhammadiyah Surakarta, 2024)
Objective: This research aims to evaluate and provide input on the ease of accessing information and making dam (penalty) payments during the Hajj pilgrimage, within the framework of Islamic law and the Sustainable Development Goals (SDGs). The study is driven by the fact that many pilgrims are still unaware of the types of violations that require dam payment and how to fulfill this obligation properly. This issue is often due to a lack of information, inadequate guidance, and limited awareness among pilgrims. Theoretical framework: The theoretical framework is based on Islamic jurisprudence regarding Hajj rituals and penalties (dam), which emphasizes justice, transparency, and individual responsibility. Literature Review: The literature review draws from classical and contemporary sources related to Hajj practices, including official guidelines, banking systems, and digital service innovations aligned with the SDGs, especially Goal 16 (Peace, Justice, and Strong Institutions). Methods: The research employs a qualitative method, incorporating firsthand observations from Hajj experiences in 2018 and 2019, as well as several Umrah pilgrimages. These are supported by secondary data from books, official documents, and online resources. Results: The findings reveal that numerous pilgrims unintentionally commit violations during key stages of the Hajj, particularly in the Armuna area (Arafah, Muzdalifah, and Mina), but do not proceed to pay the dam, primarily due to lack of knowledge or uncertainty about the payment process. Moreover, the Kingdom of Saudi Arabia has designated certain institutions such as Alrajhi Bank and Hadiyah to facilitate official dam payments. Hadiyah, in particular, offers simplified digital payment systems, making the process more accessible and transparent. Implications: The implications of this study highlight the urgent need for more structured pre-departure education for pilgrims and the integration of digital payment systems within Hajj management policies. Novelty: The novelty of this research lies in linking dam payment convenience with the broader mission of the SDGs, promoting ethical, inclusive, and accountable religious practices.